2005
DOI: 10.1097/01.brs.0000184365.28481.e3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mesenchymal Stem Cells Transplanted to a Rabbit Degenerative Disc Model

Abstract: MSCs transplanted to degenerative discs in rabbits proliferated and differentiated into cells expressing some of the major phenotypic characteristics of nucleus pulposus cells, suggesting that these MSCs may have undergone site-dependent differentiation. Further studies are needed to evaluate their functional role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
241
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 32 publications
4
241
2
2
Order By: Relevance
“…An attractive alternative for AF tissue engineering would be the use of hMSCs. However, while hMSCs can differentiate in NP cells [8,10,26], differentiation into AFCs has not been demonstrated yet. Sobajima et al [27] showed that, 24 weeks after MSCs transplantation in normal rabbit disc, MSCs were localized in the inner AF, where they exhibited an apparent change in morphology to a spindle shape more similar to native AFCs.…”
Section: Discussionmentioning
confidence: 99%
“…An attractive alternative for AF tissue engineering would be the use of hMSCs. However, while hMSCs can differentiate in NP cells [8,10,26], differentiation into AFCs has not been demonstrated yet. Sobajima et al [27] showed that, 24 weeks after MSCs transplantation in normal rabbit disc, MSCs were localized in the inner AF, where they exhibited an apparent change in morphology to a spindle shape more similar to native AFCs.…”
Section: Discussionmentioning
confidence: 99%
“…After differentiation, these cells can be placed on a gel scaffold or directly injected into the disc [73,88]. Use of bone marrowderived mesenchymal stem cells has demonstrated the ability to slow degeneration by preserving disc health as evaluated by MRI, histology, immunohistochemistry, and gene expression [44,[78][79][80]. These cells also demonstrated similar phenotypic activity to NP cells, including upregulation of aggrecan, versican, and type II collagen with suppression of the proinflammatory cytokines TNF-a and IL-1b [44].…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…10 blade along the tail to expose the lateral portions of tail discs. Human MSCs (three passages, 1 9 10 6 cells/15 lL/ segment) (Sakai et al 2006(Sakai et al , 2005(Sakai et al , 2003 were then placed into TS using a stereotactic microinjector (Harvard Apparatus; Holliston, MA, USA) and a 26 G needle at 2 weeks post injury. The same amount of saline was injected into IS.…”
Section: Ivd Degeneration and The Transplantation Of Human Mesenchymamentioning
confidence: 99%
“…However, these approaches cannot be viewed as fundamental treatments for IVD degeneration because they do not address its cause. Recently, the molecular biological characteristics of IVD degeneration were identified, and treatment strategies are being sought that regenerate IVDs by restoring extracellular matrix or cellular components in animal models (Crevensten et al 2004;Le Visage et al 2006;Sakai et al 2006Sakai et al , 2005Sakai et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation